Correcting Tibiotalar Alignment Correlates with FAO Changes after Total Ankle Replacement - Ricardo Villar MD; Emily Teehan MS; Kira Lu; Ranqing Lan MS; Patricia Friedmann MS; Jensen Henry MD; Constantine Demetracopoulos MD (Foot & Ankle Orthopaedics)
Submission Type: Ankle Arthritis Research Type: Level 3 - Retrospective cohort study, Case-control study, Meta-analysis of Level 3 studies Introduction/Purpose: Re-establishing anatomic ankle and foot alignment is critical to optimize clinical outcomes and longevity of total ankle replacement (TAR). The foot and ankle offset (FAO) is a semiautomatic 3D biometric weight-bearing computed tomography (WBCT) measurement that represents the relationship between the tripod of the foot and the center of the ankle joint. Notably, FAO correlates with increased need of additional procedures in TAR. Yet to our knowledge, no study has utilized FAO to quantify the extent to which TAR can improve alignment in the absence of foot realignment procedures. Our study aims to evaluate associations between preoperative and postoperative FAO and coronal radiograph Tibiotalar Alignment (TTA) for TAR. We hypothesize that TAR alone may significantly improve FAO in patients with ankle deformity. Methods: This study is a single-institution retrospective review of prospectively collected data from primary TARs from March 2022 – November 2023 that obtained preoperative and postoperative (between 4 months and 1 year postoperatively) WBCT scans. Patients who underwent concomitant foot realignment procedures (foot osteotomy or fusion) at the time of primary TAR were excluded. There were 85 ankles that underwent primary TAR during the study period who obtained preoperative and postoperative WBCT scans and radiographs. Excluding 23 ankles with concomitant foot realignment procedures and 7 ankles with inadequate scans, there were 55 ankles included for analysis. Patients were classified as varus, neutral or valgus using the cutoff of 5 degrees for TTA and based on the classification described by Lintz for FAO. Correlation between changes in TTA and FAO was addressed by Pearson`s correlation test. Linear regression was used to investigate the association between changes in TTA with changes in FAO. Results: Changes in TTA had a strong positive correlation (PCC 0.832, p < .0001) with changes in FAO. Every 1 degree of increase in TTA pre to post is associated with 0.367 unit increase in FAO pre to post (R^2 0.693, p < 0.0001). In terms of TAR ability to improve FAO, there was a median pre to post FAO change of 2.66 [-0.11, 5.86] for the varus pre-op FAO group and of − 4.69 [-7.52, -2.985] for the valgus pre-op FAO group. Postoperatively, 80% of patients that had pre-op varus FAO remained varus, while 59% that had pre-op neutral FAO persisted neutral and 22% that had pre-op valgus FAO stayed valgus. 98% of patients had neutral post TTA, confirming coronal alignment improvement with TAR. Conclusion: In this study, with each 1-degree change in TTA, there was a 0.367 change in FAO with a strong positive correlation between the 2D and the 3D measurements. TAR was able to improve FAO in patients with tibiotalar deformity and a more powerful change was noticed in valgus alignment. After TAR, patients with pre-op varus FAO are most likely to remain varus, while patients with valgus pre-op FAO are most likely to improve to neutral FAO. Understanding how FAO changes after TAR can help surgeons predict when an additional procedure could be necessary.